PENERAPAN MEDIA ROLE PLAYING UNTUK MENINGKATKAN SIKAP KERJASAMA - Rahmahwati Nurul Utami; Saharani Wulandari; Wahyu Setiyo Asih; Iffah Muslimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the effectiveness of the application of role-playing media to improve cooperative attitude skills. Students will be the center of learning because they are the subjects of learning. The research method used is classroom action research with a qualitative approach. The results of the study aim to show that the use of immersive media can significantly improve students' cooperative attitudes. Students become more active in communicating, supporting each other and collaborating to complete group assignments. Based on this study, multimedia role-playing games are applied as an effective method to improve students' cooperative attitudes in learning. This study suggests that teachers be more creative in using interactive learning methods so that they significantly encourage students' cooperative attitudes. The use of role-playing learning can also improve students' speaking skills and academic achievement. Therefore, in the learning process, teachers should use the role play learning model, because in addition to improving speaking skills and learning outcomes, it can also be more optimal.